Youth on the Frontier of Precariousness: Income and Inequality in the Labor Market - Velázquez Barrón, Marilú Yatzael (Revista Internacional de Salarios Dignos, 2025)
The precariousness of youth labor in the Mexican market has been accentuated in recent decades, representing a significant challenge for public policies. This study aims to analyse the impact of income and structural inequality on young people’s working conditions, with an emphasis on wage disparities and the prevalence of informal and precarious jobs. Through a quantitative approach and the application of logistic regression models (logit), data from official sources are analyzed to identify the main socioeconomic variables that affect the working conditions of young people, such as educational level, type of employment, and characteristics of the economic sector. The results reveal that young people with a lower level of education and those employed in the informal sector are more likely to face wage inequality and precarious working conditions. The main contribution of this study lies in offering a comprehensive view of the factors that promote youth job insecurity and providing recommendations for public policies aimed at reducing wage gaps and improving the quality of youth employment. As a limitation, the possible presence of endogeneity in some variables is recognized, so the results should be interpreted as statistical associations and not as causal inferences.